1988
DOI: 10.1136/gut.29.7.949
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of immunologically mediated enteropathy. Development of cell mediated immunity and intestinal pathology during a graft-versus-host reaction in irradiated mice.

Abstract: SUMMARYThe intestinal component of a graft-versus-host reaction (GvHR) provides a useful experimental model to elucidate the pathogenesis of clinical enteropathies which cause villus atrophy and crypt hyperplasia and which are associated with a local immune response. One to three days after induction of GvHR in heavily irradiated (CBAxBALB/c)F, mice, a proliferative form of enteropathy developed. Compared with controls, these mice had increased counts of jejunal intraepithelial lymphocytes and had a four-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Therefore, to compare the numbers of i-IEL between mice given anti-TcR y6 mAb or control mAb during acute GVHD, the number of 1-IEL per 100 epithelial cells was counted under the light microscope. Consistent with our previous report, the 1-IEL counts temporarily increased on day 9, and thereafter declined remarkably on day 12 following acute GVHD induction in control mice. On the other hand, a significant increase of 1-IEL was not evident on day 9 and only a marginal decrease was detected in the mice given anti-TcR y6 mAb (Fig.…”
Section: Kinetics Of Host-derived I-iel After Acute Gvhd Induction Insupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, to compare the numbers of i-IEL between mice given anti-TcR y6 mAb or control mAb during acute GVHD, the number of 1-IEL per 100 epithelial cells was counted under the light microscope. Consistent with our previous report, the 1-IEL counts temporarily increased on day 9, and thereafter declined remarkably on day 12 following acute GVHD induction in control mice. On the other hand, a significant increase of 1-IEL was not evident on day 9 and only a marginal decrease was detected in the mice given anti-TcR y6 mAb (Fig.…”
Section: Kinetics Of Host-derived I-iel After Acute Gvhd Induction Insupporting
confidence: 91%
“…Unusual target organs such as the skin and intestine are first affected during acute graft-versus-host disease (GVHD), which is initiated by donor-derived mature T cells recognizing alloantigens on host cells [9] .The fact that TcR y6 T cells are relatively abundant in the epithelia of the epidermis and the intestine raises the possibility that unique IEL partici-pate in the pathogenesis of epithelial lesions during acute GVHD. To verify this, we examined the kinetics of TcR y6 i-IEL during the course of acute GVHD caused in inbred F1 mice by injecting them with T cells of parental origin.…”
Section: Lntroductionmentioning
confidence: 99%
“…This could be a reflection of sparse immune complex deposition in the intestinal mucosa, as suggested by our radiotracer experiments. In other ex perimental animal models, enteropathies similar to those seen in coeliac disease have been observed after the in duction of graft-versus-host disease [25]. It is therefore possible that an immune-mediated enteropathy also re quires a cell-mediated component and cannot be induced by circulating antibody alone.…”
Section: Discussionmentioning
confidence: 92%
“…Taken together, the available data suggest that im mune-mediated intestinal damage involves an autoim mune element, either due to circulating antibodies to tis sue components [21][22][23][24], or due to cell-mediated immunity against self-antigens [25], or possibly both. This would imply that elevated anti-gliadin antibody titres in patients with coeliac disease may be a contributory factor, but alone arc unlikely to mediate the intestinal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In immu nocompetent animals not previously irra diated this has been generally the most severe enteropathy produced by GvHR. However, in allograft rejection and in some immunodeficient animals, a destructive lesion with vil lus flattening in addition to crypt hyperplasia and IEL infiltrate occurs and Mowat et al [1988] report crypt hypoplasia early in the course of GvHR in irradiated mice. In a recent experiment we have found that a com plete spectrum of histopathological changes develop in adult BDFi mice studied at inter vals up to five weeks after induction of GvHR [Watret and Ferguson, unpublished].…”
Section: Recommended Terms For the Description Of Immune-mediated Intmentioning
confidence: 99%